Nanobubbles explain the large slip observed on lubricant-infused surfaces - Christopher Vega-Sánchez; Sam Peppou-Chapman; Liwen Zhu; Chiara Neto (Nature Communications, 2022)
Why are lubricant-infused surfaces so effective at reducing drag in microfluidic flow? Here, authors reveal that infused nanostructured Teflon wrinkles induce large interfacial slip due to the spontaneous nucleation of surface nanobubbles, a mechanism likely to occur on most rough infused surfaces.